MANAJEMEN PROSES KONVERSI PERBANKAN KONVENSIONAL MENJADI PERBANKAN SYARIAH STUDI KASUS BANK NTB SYARIAH - Ikono, Radyum; Reno Kemala Sari, Putri (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
won the 2019 Global Islamic Financial Report (GIFR) Award.The development of the Islamic banking industry has been welcomed by service usersbanking, especially the province of West Nusa Tenggara (NTB) withthe success of the NTB Regional Development Bank (BPD) in converting toBank NTB Syariah on September 4 2018, this conversion is an innovationmajor in Indonesian banking. This study aims to determinemanagement process carried out by Bank NTB Syariah in controlling ResourcesHuman Power at each conversion stage according to Lewin's model of change.This research is a descriptive qualitative researcha case study approach to the conversion of Bank NTB Syariah. Source of dataused are primary and secondary data, namely by interview technique, studylibraries, documentation studies, and internet searching. The results of this studyconcluded that the conversion process of Bank NTB Syariah was going well.Process management is carried out with care and considerationpreparation and implementation, development of SDI, performance of Bank NTB Syariah, as wellgood documentation. At every stage of the conversion it must always motivate SDIexisting in order to stay on the desired conversion system in a waycarry out training, conduct benchmarks and collaborate withother institutions. Post-conversion Bank NTB Syariah experienceda significant performance increase, with a hugely improved DPK portraitsignificant, which is approximately 40% of the average growth each year.